Yeast transformation efficiency is enhanced by TORC1‐ and eisosome‐dependent signaling - Yu, Sheng‐Chun (Microbiologyopen, 2018)
Transformation of baker's yeast (Saccharomyces cerevisiae) plays a key role in several experimental techniques, yet the molecular mechanisms underpinning transformation are still unclear. The addition of amino acids to the growth and transformation medium increases transformation efficiency. Here, we show that target of rapamycin complex 1 (TORC1) activated by amino acids enhances transformation via ubiquitin‐mediated endocytosis. We created mutants of the TORC1 pathway, alpha‐arrestins, and eisosome‐related genes. Our results demonstrate that the TORC1‐Npr1‐Art1/Rsp5 pathway regulates yeast transformation. Based on our previous study, activation of this pathway results in up to a 200‐fold increase in transformation efficiency, or greater. Additionally, we suggest DNA may be taken up by domains at the membrane compartment of Can1 (MCC) in the plasma membrane formed by eisosomes. Yeast studies on transformation could be used as a platform to understand the mechanism of DNA uptake in mammalian systems, which is clinically relevant to optimize gene therapy.